Ingestion of Milk Containing Very Low Concentration of Antimicrobials: Longitudinal Effect on Fecal Microbiota Composition in Preweaned Calves. - Richard Van Vleck Pereira; Svetlana Lima; Julie D Siler; Carla Foditsch; Lorin D Warnick; Rodrigo Carvalho Bicalho (PLoS ONE, 2016)
Although antimicrobial drugs are central to combat disease in modern medicine, the use of these drugs can have undesired consequences for human and animal health. One consequence is the post-therapy excretion of pharmacological agents, such as the elimination of drug residues at very low concentrations in the milk of lactating mammals. Limited information is currently available on the impact from the exposure of the gut microbiota to drug residues using in vivo natural models. The objective of our study was to address this knowledge gap and evaluate the effect on the fecal microbiota composition from feeding preweaned dairy calves raw milk with residual concentrations of ampicillin, ceftiofur, penicillin, and oxytetracycline from birth to weaning. At birth, thirty calves were randomly assigned to a controlled feeding trial where: 15 calves were fed raw milk with no drug residues (NR), and 15 calves were fed raw milk with drug residues (DR) by adding ceftiofur, penicillin, ampicillin, and oxytetracycline at final concentrations in the milk of 0.1, 0.005, 0.01, and 0.3 μg/ml, respectively. Fecal samples were rectally collected from each calf once a week starting at birth, prior to the first feeding in the trial (pre-treatment), until 6 weeks of age. Sequencing of the microbial 16S rRNA genes was conducted using the Illumina MiSeq, which provides a high resolution of the microbiota down to the genus level. Discriminant analysis showed that, except for pre-treatment samples, calves fed milk with drug residues and calves fed milk without drug residues easily discriminated at the genus level on their weekly microbial profile. However, analysis comparing the abundance of taxon between NR and DR showed significant differences only at the genus levels, and not at the phylum, class, order or family levels. These results suggest that although drug residues can result in clear discriminate gut microbial communities, they do not result in disruption of taxonomic levels above the genus.